Hubungan Bimbingan Belajar dengan Prestasi Belajar Siswa dan Implikasinya dalam BK di SMP Negeri 33 Kerinci - Fendry Fendry; Satya Anggi Permana; Niko Reski (Departement of Mathematics Education, 2024)
This research is motivated by many students who get scores below the Minimum Completeness Criteria, this is based on the results of even semester scores of SMP Negeri 33 Kerinci students in grades VIII and IX, namely many students who get unfinished criteria. Some students cannot understand the material provided by the teacher. In learning and teaching activities there are students who skip classes during class hours, make noise that makes other students less concentrated and students who disturb friends and leave during teaching and learning activities. The purpose of this study is to describe learning guidance, describe learning achievement and describe the relationship between learning guidance and student learning achievement and its implications in BK at SMP Negeri 33 Kerinci. This research is quantitative research and this type of research is descriptive correlational research consisting of two variables, namely the variable of study guidance and learning achievement variables, where the population in this study were all students of SMP Negeri 33 Kerinci totalling 104 people. The sample in this study were VIII and IX grade students totalling 61 students. Data collection was taken from distributing questionnaires with a Likert Scale. The validity test in this study is using Product Moment Corelation and reliability test using Alpha Cronbach. Data analysis techniques in this study used normality test, linearity test and hypothesis testing. Based on the results of the research that has been done, the correlation coefficient is 0.419> 0.279 with a significance price = 0.002 (sig <0.01). From the analysis of the coefficient of determination, the results obtained are 17.56% so that emotional intelligence has an effect of 17.56% on improving learning achievement in students of SMK Negeri 2 Kerinci. It can be concluded that, there is a relationship of tutoring with student learning achievement and its implications in BK at SMP Negeri 33 Kerinci.